Evolutionary origins of abnormally large shoot sodium accumulation in non-saline environments within the Caryophyllales - White, Philip J.; Bowen, Helen C.; Broadley, Martin R.; El-Serehy, Hamed A.; Neugebauer, Konrad; Taylor, Anna; Thompson, Jacqueline A.; Wright, Gladys (Wiley, 2016)
The prevalence of sodium (Na) “hyperaccumulator” species, which exhibit abnormally large shoot sodium concentrations ([Na]shoot) when grown in non-saline environments, was investigated among angiosperms in general and within the Caryophyllales order in particular.